Analisis Kualitas Pelayanan Publik Pada Telkom Di Kabupaten Tana Toraja - Susandi Kalaba; Isak Pasulu; Dwibin Kannapadang (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This study aims to obtain an overview of the quality of public service at Telkom in Tana Toraja Regency by using the service quality dimension. The design of this research is descriptive. The data taken in this study usea a questionnaire method, observation and documentation conducted at Telkom in Tana Toraja Regency. The result of this study indicate that the quality of public services at Telkom in Tana Toraja Regency is of good quality. Where from the five dimensions of service quality used to measure service quality, namely the Tangiabel dimension is in the good attitude category, the Reability dimension is in the good attitude category, the Responsiveness dimension is in the good attitude category, the Assurance dimension is in the good attitude category and the Empathy dimension is in the very good attitude category.